The Effect of Sustainability Information Disclosure on Financial and Market Performance: Empirical Evidence from Indonesia and Malaysia - Hardiningsih, Pancawati; Januarti, Indira; Yuyetta, Etna Nur Afri; Srimindarti, Ceacilia; Udin, Udin (International Journal of Energy Economics and Policy, 2020)
This study aims to analyze the effect of sustainability information disclosure on financial and market performance. Using purposive sampling, this study obtains 21 mining sector companies in Indonesia and 18 companies in Malaysia. Regression analysis with WarpPLS is used to test the proposed hypotheses. The results show that environmental and social disclosure has a significant effect on return on assets (ROA), return on equity (ROE), price-earnings ratio, and Tobin'Q in Indonesia and Malaysia. Overall, there is no significant difference in financial and market performance between Indonesia and Malaysia. Good sustainability information disclosure further improves financial performance and trust among stakeholders and regulators in decision making, which in turn, increases corporate value. Keywords: Environmental disclosure, social disclosure, financial performance, corporate value JEL Classifications: E44, M14, Q56 DOI: https://doi.org/10.32479/ijeep.8520